L’apport de deux études empiriques à la conceptualisation du “collectif”. De quel collectif parle‑t‑on et comment saisir son activité ? - Sylvie Moussay; Éric Flavier (Activités)
The article is a theoretical contribution to the purpose and activity of a collective. Drawing inspiration from research in the field of work analysis, our objective is to examine the collective, its emergence and its organization whose reality and actors’ experiences still need to be grasped if we are to enhance theoretical and methodological progress. Empirical illustrations inform two questions: “Which collective(s) are we talking about?” and “How can we capture collective activity?” Referring to the cultural historical approach based on the development of activity (Vygotsky, 1997), the two studies apprehend the collective in different work contexts: a collective of persons designing a digital training platform on the one hand, and a group of trainers training novice teachers on the other. The results make it possible to consider the collective as an emergent, fragile and uncertain entity, based on a specific intention in which every constituent person takes part, and which is organized around the processes of affiliation and contractual grouping.